A review of the Cyana phaedra (Leech, 1889) species-group, with description of a new species from China (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V. (Zootaxa, 2021)
The Cyana phaedra (Leech, 1889) species-group is reviewed. The group is closely related to the C. dohertyi (Elwes, 1890) species-group. A new species, C. leechi sp. nov. is described from Sichuan, southwestern China. Bizone phaedra var. moupinensis Leech, 1899 is upgraded to species level: C. moupinensis (Leech, 1899), stat. nov. The lectotype is designated for Bizone phaedra Leech, 1889.